ChemInform Abstract: Dimorphic EuCu5Cd. Issue 2 (9th January 2013) - Tappe, Frank; Schwickert, Christian; Poettgen, Rainer
Abstract Two modifications of the title compound are prepared from the elements in sealed tantalum ampules and characterized by single crystal XRD and magnetic measurements.